STRATEGI DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS MELALUI SINERGI KEBIJAKAN FISKAL DAN MONETER ISLAM - Nia Dwi Rahayu Putri; Eka Wahyu Firmansyah; Shofiya Zevania Putri; Silvia Fatika Sari; Amalia Nuril Hidayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article examines strategies for achieving the Sustainable Development Goals (SDGs) through the synergy of Islamic fiscal and monetary policies grounded in principles of justice, sustainability, and economic stability. Using a descriptive qualitative method based on literature reviews of journals, books, and policy documents, the study analyzes the roles of zakat, infaq, waqf, Islamic sukuk, and sharia-based monetary operations in supporting sustainable development. The findings show that Islamic fiscal policies significantly contribute to reducing poverty, improving income distribution, and strengthening education and health sectors through more equitable wealth allocation. Meanwhile, Islamic monetary policies promote price stability, expand productive financing, and support environmentally friendly infrastructure development through green and social sukuk instruments. Digitalization, Islamic fintech, and transparent governance also enhance financial inclusion and improve the effectiveness of sharia-based economic policies. Overall, the study concludes that the synergy between Islamic fiscal and monetary policies provides an effective and practical strategy to accelerate SDG achievement because it offers an economic framework that is equitable, inclusive, stable, and oriented toward community empowerment and long-term sustainability.